CSR Practices of PLN Nusantara Power Unit Pembangkitan Paiton Through the Lestari Bumi Harmoni Program in Binor Village - Yudha, Ananda Satria Oka; Pramartha, Martinus Tega Ardhi (Global Writing Academica Researching and Publishing, 2024)
This research contains about the implementation of the Lestari Bumi Harmoni Program in Binor Village. This research aims to explain the corporate social responsibility program of PLN Nusantara Power Unit Pembangkitan Paiton through community empowerment. The problems that occur in Binor Village include unprocessed food waste, forest and land fires, poaching that can damage the environment, and community welfare. Meanwhile, the main potential of Binor Village is the wealth and diversity of flora and fauna. This research method uses descriptive qualitative. Data collection techniques were carried out by interview, observation, and documentation study. The data in this study were analyzed using the concept of five steps of CSR program initiation and three points of community empowerment implementation. The impact of this program is not only on the environmental aspect but also on social and economic aspects such as increasing community income, saving expenses, and increasing community knowledge and skills. The community group managing the program is expected to be able to continue the program independently so that the benefits of the program can be felt in the long term. This shows the success of the PLN Nusantara Power Unit Pembangkitan PaitonCSR program in implementing community empowerment activities in Binor Village.